2017
DOI: 10.1002/mnfr.201700440
|View full text |Cite
|
Sign up to set email alerts
|

(‐)‐Epigallocatechin‐3‐gallate Ameliorates Insulin Resistance and Mitochondrial Dysfunction in HepG2 Cells: Involvement of Bmal1

Abstract: The results demonstrated that EGCG possesses a Bmal1-dependent efficacy against insulin resistance conditions by strengthening the insulin signaling and eliminating oxidative stress, suggesting that EGCG may serve as a promising natural nutraceutical for the regulation of metabolic disorders relevant to circadian clocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 58 publications
(95 reference statements)
2
43
0
1
Order By: Relevance
“…Hyperglycemia-mediated mitochondrial superoxide overproduction can suppress the activity of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and it meanwhile leads to the activation of the hexosamine pathway with the increasing influx of phosphorylated glucose [ 87 , 88 ]. High glucosamine generated by the activation of hexosamine pathway stimulates the overproduction of ROS in mitochondria and damages mitochondrial respiration [ [89] , [90] , [91] ], which can further aggravate oxidative stress, augment vascular permeability, and promote angiogenesis.…”
Section: Oxidative Stress and The Abnormalities Of Polyol/pkc/age Formentioning
confidence: 99%
“…Hyperglycemia-mediated mitochondrial superoxide overproduction can suppress the activity of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and it meanwhile leads to the activation of the hexosamine pathway with the increasing influx of phosphorylated glucose [ 87 , 88 ]. High glucosamine generated by the activation of hexosamine pathway stimulates the overproduction of ROS in mitochondria and damages mitochondrial respiration [ [89] , [90] , [91] ], which can further aggravate oxidative stress, augment vascular permeability, and promote angiogenesis.…”
Section: Oxidative Stress and The Abnormalities Of Polyol/pkc/age Formentioning
confidence: 99%
“…In addition, the compensatory growth of β-cells caused by diet-induced obesity-related insulin increases is controlled by Bmal1 ( Rakshit et al, 2016 ). These observations suggest that the core circadian gene Bmal1 is involved in fatty acid synthesis and the β-oxidation pathway ( Mi et al, 2017b ). Therefore, regulating circadian rhythm disorders caused by alcohol feeding may be a treatment target for ALD.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, regulating circadian rhythm disorders caused by alcohol feeding may be a treatment target for ALD. The studies have discovered that EGCG and tea polyphenols reduce insulin resistance in a Bmal1-dependent way and by activating AMPK signaling pathways ( Mi et al, 2017a ; Mi et al, 2017b ). Besides, proanthocyanidins can regulate circadian gene expression in cultured fibroblasts ( Ribas-Latre et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Food components, such as glucose, sodium, amino acids, caffeine, thiamine, and ethanol, are capable of resetting or phase-shifting circadian rhythms [39,40]. Mi et al found that EGCG (a biologically active component in green tea) can regulate glucosamine-induced HepG2 hepatocyte IR via the core circadian protein Bmal1 [23]. In db / db mutant mice, the clock is also obligated for the remitting effects of nobiletin on metabolic disorders [37].…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive components in natural foods, such as proanthocyanidins, (-)-Epigallocatechin-3-gallate (EGCG), chicoric acid, and nobiletin, can manipulate circadian rhythms to ameliorate metabolic syndrome [21,22,23]. Resveratrol (RES, 3,5,4′-trihydroxystilbene), a natural product derived from grapes, has various health benefits, including anti-inflammatory, anti-oxidant, and anti-mutation properties [24].…”
Section: Introductionmentioning
confidence: 99%